The (Parlous) State of German Unions - Addison, John T.; Schnabel, Claus; Wagner, Joachim (Journal of Labor Research, 2007)
This paper traces the profound decline in German unionism over the course of the last three decades. Today just one in five workers is a union member, and it is now moot whether this degree of penetration is consistent with a corporatist model built on encompassing unions. The decline in union membership and density is attributable to external forces that have confronted unions in many countries (such as globalization and compositional changes in the workforce) and to some specifically German considerations (such as the transition process in post-communist Eastern Germany) and sustained intervals of classic insider behavior on the part of German unions. The "correctives" have included mergers between unions, decentralization, and wages that are more responsive to unemployment. At issue is the success of these innovations. For instance, the trend toward decentralization in collective bargaining hinges in part on the health of that other pillar of the dual system of industrial relations, the works council. But works council coverage has also declined, leading some observers to equate decentralization with deregulation. While this conclusion is likely too radical, German unions are at the cross roads. It is argued here that if they fail to define what they stand for, are unable to increase their presence at the workplace, and continue to lack convincing strategies to deal with contemporary economic and political trends working against them, then their decline may become a rou
WiSo-Import:2015-03-26:1746